Toxicological evaluation of a saponin-rich standardized extract of fenugreek seeds (FenuSMART®): Acute, sub-chronic and genotoxicity studies. (2018) - Sureshkumar, D.; Begum, Shamshad; Johannah, N.M.; Maliakel, Balu; Krishnakumar, I.M.
Graphical abstract: Highlights: Safety evaluation of a standardized extract of fenugreek seeds (FenuSMART). Acute and subchronic oral toxicity studies of FenuSMART on Wistar rats. Mutagenicity study of FenuSMART. Abstract: The present study investigated the safety of a saponin-rich standardized extract of fenugreek seeds (FenuSMART ® ; FHE), that has been clinically shown to be effective in ameliorating the postmenopausal discomforts and establishing hormonal balance. The safety was assessed by oral acute (2500 mg/kg b. wt. for 14 days) and subchronic (250, 500 and 1000 mg/kg b. wt. for 90 days) toxicity studies on Wistar rats and mutagenicity studies employing Salmonella typhimurium strains. Administration of FHE did not produce any toxicologically significant changes in clinical/behavioral observations, ophthalmic examinations, body weight, organ weight, feed consumption, urinalysis, hematology and clinical biochemistry parameters when compared to the untreated control group of animals. Highest dose recovery group (1000 mg/kg b. wt.) of animals also showed no mortality or adverse events; with hematological and biochemical parameters at par with those of controls. Terminal autopsy revealed no alterations in relative organ weight or any treatment-related histopathology changes. FHE also showed no mutagenicity upon Ames test employing TA-98, TA-100 and TA-102 Salmonella typhimurium strains with or without metabolic activation. Based on the results of the study, the no observed-adverse-effect level (NOAEL) of FHE was determined as 1000 mg/kg b. wt./day, the highest dose tested.